A risk metric for designing a highly reliable real-time Ethernet network - Lei Zhang; Lehmann, R.; Zhi Wang (2009 IEEE Conference on Emerging Technologies & Factory Automation, 2009)
The recent developments of industrial Ethernet are brushing aside people's doubt whether industrial Ethernet could fulfill all of their requirements to real-time performance and reliability. Although designing a highly reliable network with strict real-time constraints is becoming possible, no method has been proposed to help network design systematically considering reliability and real-time constraints. A risk metric is proposed in this paper for evaluating the relationship between reliability mechanisms of an industrial Ethernet network and its real time performance. By simulation of an example network with ring topology the metric is shown to be a suitable basis for effective network optimization.